2017
DOI: 10.4132/jptm.2017.04.05
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Bethesda System for Reporting Thyroid Cytopathology in Korea: A Nationwide Multicenter Survey by the Korean Society of Endocrine Pathologists

Abstract: BackgroundThe Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) has standardized the reporting of thyroid cytology specimens. The objective of the current study was to evaluate the nationwide usage of TBSRTC and assess the malignancy rates in each category of TBSRTC in Korea. MethodsQuestionnaire surveys were used for data collection on the fine needle aspiration (FNA) of thyroid nodules at 74 institutes in 2012. The incidences and follow-up malignancy rates of each category diagnosed from January t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 26 publications
5
27
1
Order By: Relevance
“…Proportions (average and range) of FNA samples in Korean practice were slightly high for AUS/FLUS at 9.7% (3.8%‐19.8%) and very low for FN/SFN at 0.9% (0%‐2.1%), which were reported in several previous studies from Korea . Average RRs of the six Bethesda categories were 14.3% (non‐diagnostic), 2.4% (benign), 20.2% (AUS/FLUS), 43.7% (FN/SFN), 59.9% (SM) and 69.2% (malignant), respectively . The average ROMs for the six Bethesda categories were 46.5% (non‐diagnostic), 16.5% (benign), 68.7% (AUS/FLUS), 30.2% (FN/SFN), 97.5% (SM) and 99.7% (malignant), respectively .…”
Section: Review Of Reports By Members Of the Working Group Of Asian Tsupporting
confidence: 60%
See 4 more Smart Citations
“…Proportions (average and range) of FNA samples in Korean practice were slightly high for AUS/FLUS at 9.7% (3.8%‐19.8%) and very low for FN/SFN at 0.9% (0%‐2.1%), which were reported in several previous studies from Korea . Average RRs of the six Bethesda categories were 14.3% (non‐diagnostic), 2.4% (benign), 20.2% (AUS/FLUS), 43.7% (FN/SFN), 59.9% (SM) and 69.2% (malignant), respectively . The average ROMs for the six Bethesda categories were 46.5% (non‐diagnostic), 16.5% (benign), 68.7% (AUS/FLUS), 30.2% (FN/SFN), 97.5% (SM) and 99.7% (malignant), respectively .…”
Section: Review Of Reports By Members Of the Working Group Of Asian Tsupporting
confidence: 60%
“…They found that 60 (81%) out of 74 pathology laboratories in Korea used the Bethesda system as of 2012, which was a higher rate than in US practice reported in 2013 by the College of American Pathologists and 94% (34/36) in 2016 . Proportions (average and range) of FNA samples in Korean practice were slightly high for AUS/FLUS at 9.7% (3.8%‐19.8%) and very low for FN/SFN at 0.9% (0%‐2.1%), which were reported in several previous studies from Korea . Average RRs of the six Bethesda categories were 14.3% (non‐diagnostic), 2.4% (benign), 20.2% (AUS/FLUS), 43.7% (FN/SFN), 59.9% (SM) and 69.2% (malignant), respectively .…”
Section: Review Of Reports By Members Of the Working Group Of Asian Tmentioning
confidence: 96%
See 3 more Smart Citations